The Effects of Team-Orientation of the Organizations on the Increase in Organizational learning and Management Effectiveness (Case Study: Maskan Bank, West Azarbaijan Province) - Parivash Mohammadi Gheshlagh (Journal of Global Pharma Technology, 2016)
This study aims to investigate the effects of team-orientation of the organizations on the increase in organizational learning and management effectiveness of the staff worked in the Maskan Bank in West Azarbaijan Province. The population of this study included the staff of Maskan Banks in West Azarbaijan Province (322 staff). The sample size was estimated equal to 175 staff by the use of Cochran formula and stratified random sampling method. Data collection tools were the standard team-orientation inventory, standard organizational learning inventory and standard management effectiveness inventory which were used after investigating their validities and reliabilities. Their reliabilities were estimated equal to 0.849. The inventories were collected and the obtained data was classified and analyzed by the use of descriptive and inferential statistics (path analysis with SPSS software and Amos software). The results of path analysis showed that the dimensions of organization’s team-orientation indirectly affect the management effectiveness through the increased organizational learning in Maskan Bank in West Azarbaijan Province.Key words: organization’s team-orientation, management effectiveness, organizational learning